No evidence that carotenoid pigments boost either immune or antioxidant defenses in a songbird - Rebecca E. Koch (Nature Portfolio, 2018)
Dietary carotenoids have been proposed to have physiological benefits in addition to contributing to coloration. Here, Koch et al. compare immune and antioxidant functions in yellow, carotenoid-rich vs. white, carotenoid-deficient canaries and find no difference, suggesting a limited physiological role of carotenoids.